A COMPARATIVE ANALYSIS OF INFORMATION SECURITY INCIDENTS IN PUBLIC ADMINISTRATION IN SELECTED EUROPEAN UNION COUNTRIES - Lisiak-Felicka, Dominika (Management and Administration Journal, 2024)
The article presents the issue of information security incident management in public administration. The goal of security incident management is to minimize the negative impact of incidents and ensure the continuity of the organization’s operations. It is critical to know what the threats are, including the number and types of incidents reported. The article outlines key incident management and legal issues related to the topic of security incidents and the work of computer incident response teams. Examples of incidents that took place recently in public administration units in Poland were also presented. This was followed by an analysis of statistical data on reported incidents in Poland in the years 2020-2022, and the results were compared with the number of incidents reported in selected European Union countries. The results of the study show that the dominant type of incidents is fraud (mainly phishing), and public administration is one of the main targets of cybercriminals’ attacks. Difficulties in conducting such comparative analysis have also been demonstrated.